Inovasi, Proaktivitas, dan Keberanian Mengambil Risiko sebagai Kunci Sukses dalam Memulai dan Mengelola Usaha - Az Zahra, Dinda Fadia; Sianturi, Risbon; Agustin, Ineu; Fauziah, Nurwati (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2024)
This article explores the important role of innovation, proactivity, and risk-taking courage as key pillars of success in starting and managing a business. AFD Collection is a fashion business established in the midst of the COVID-19 pandemic. This business not only survived through difficult times but also managed to grow by utilizing product innovation, digital marketing strategies, and proactivity in responding to rapidly changing market dynamics. Innovation allows companies to create products that fit trends, while proactivity encourages adaptation and the search for new opportunities. In addition, the courage to take risks is a vital element in facing business uncertainty and challenges. This article also examines how human resource management and digital technology optimization can improve productivity and efficiency, and offers advice for entrepreneurs to strengthen their position in the increasingly fierce competition. Innovation, proactivity, and careful risk-taking are powerful combinations to achieve success in entrepreneurship, especially in the context of volatile and challenging markets.